Why distractors with need-supportive content can mitigate ironic effects of thought suppression - Wang, Deming; Chatzisarantis, Nikos; Hagger, Martin (Springer Netherlands, 2017)
Thought suppression is a self-regulatory strategy commonly used to avoid unwanted thoughts although it can ironically make unwanted thoughts more intrusive and accessible. To reduce these ironic effects, it is important to explore mechanisms underlying effective suppression. The present study recruited 126 undergraduate students and examined the influence of distractor content on suppression outcomes by examining perceived satisfaction and immersion of distractors as mechanisms of effective suppression. Based on self-determination theory, we proposed that distractors associated with the satisfaction of the psychological need for autonomy would mitigate ironic effects of thought suppression because they would be perceived as satisfying and immersive. Results showed that need-supportive distractors reduced intrusion frequency because they were indeed perceived as more satisfying. Our findings also point towards the unique satisfying properties of distractors involving psychological need satisfaction because effects of single, pleasant and personally relevant distractors have been controlled for. Findings are discussed using Wegner’s (Psychological Review 101:34–52, 1994) theories of thought suppression and principles of self-determination theory.